2016
DOI: 10.1310/sci2016-00012
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Caregiver Characteristics and Health-Related Quality of Life Among Youth with Spinal Cord Injury

Abstract: Past research has found a relationship between the mental health of parental caregivers and their children with spinal cord injury (SCI), but little is known about how other aspects of caregiver health and functioning impact health-related quality of life (HRQOL) of youth. The purpose of this study was to explore the importance of caregiver mental health, physical health, burden, and problem-solving skills in relation to children's physical and psychosocial HRQOL. Forty youths with SCI ages 7 to 17 years compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Identified secondary stressors included impacts on the family (including balancing roles and emotional distress), social networks, financial stability, and the caregivers' own self-care. Data also highlighted support from both professionals and peers as resources that could potentially serve as mediators between stressors and caregiver well-being; this builds on past research that has identified the importance of caregiver problem solving skills [3,22]. Fleshing out these components of stress theory model in the specific context of caregiving and pediatric SCI can help lead to the development of comprehensive models of intervention to support caregivers of youth with SCI.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Identified secondary stressors included impacts on the family (including balancing roles and emotional distress), social networks, financial stability, and the caregivers' own self-care. Data also highlighted support from both professionals and peers as resources that could potentially serve as mediators between stressors and caregiver well-being; this builds on past research that has identified the importance of caregiver problem solving skills [3,22]. Fleshing out these components of stress theory model in the specific context of caregiving and pediatric SCI can help lead to the development of comprehensive models of intervention to support caregivers of youth with SCI.…”
Section: Discussionmentioning
confidence: 89%
“…Challenges associated with caregiving across a variety of chronic illnesses and disabilities are widely documented and include the toll on caregiver physical and emotional health and quality of life (QOL) [2]. Attending to the complex health and unmet needs of caregivers is vital to the overall health of the caregiver, as well as the functioning of the child and the entire family unit [3][4][5][6][7]. Lazurus and Folkman's stress and coping model [8] and Pearlin and colleagues' stress process model [9,10] examine the nature of stressors and how internal resources (e.g., coping) and external resources (e.g., social support) can influence how stress impacts health and well-being.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research shows the connection between caregiver wellbeing (physical and mental) and child functioning. 4 Consequently, failure to detect and address caregiver and family distress may lead to further decline in the caregiver, child, and family placing additional burden on the local community and larger healthcare system. As professionals, we are in a unique position with families when caring for their child; we are bestowed with long-term trust, affording us opportunities to identify caregiver and family distress, provide support and guidance, and monitor change over time.…”
Section: Perspectives On Caring For the Child And The Caregivermentioning
confidence: 99%